2017
DOI: 10.3390/en10040420
|View full text |Cite
|
Sign up to set email alerts
|

Improved Separation and Collection of Charge Carriers in Micro-Pyramidal-Structured Silicon/PEDOT:PSS Hybrid Solar Cells

Abstract: Silicon (Si)/organic polymer hybrid solar cells have great potential for becoming cost-effective and efficient energy-harvesting devices. We report herein on the effects of polymer coverage and the rear electrode on the device performance of Si/poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate) (PEDOT:PSS) hybrid solar cells with micro-pyramidal structures. These hybrid solar cells provided adequate generation of charge carriers owing to the suppression of reflectance to below 13%. Additionally, the sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…For the Si substrate with such micro-textured surfaces, the PEDOT:PSS layer, which is a p-type-like conjugated conducting polymer, was spin-coated at a spin speed of 7500 rpm. We have previously confirmed that for micro-pyramidal structures [11] and nanowire array structures [19] this spin speed enables the PEDOT:PSS layer to better adhere on micro-textured surfaces. The morphology of the PEDOT:PSS layer on the micro-desert textured surfaces and honeycomb surfaces was analyzed by means of cross-sectional SEM micrographs, as shown in Figures 2a and 2b, respectively.…”
Section: Morphology and Antireflection Effect Of Si/pedot:pss Composimentioning
confidence: 66%
See 2 more Smart Citations
“…For the Si substrate with such micro-textured surfaces, the PEDOT:PSS layer, which is a p-type-like conjugated conducting polymer, was spin-coated at a spin speed of 7500 rpm. We have previously confirmed that for micro-pyramidal structures [11] and nanowire array structures [19] this spin speed enables the PEDOT:PSS layer to better adhere on micro-textured surfaces. The morphology of the PEDOT:PSS layer on the micro-desert textured surfaces and honeycomb surfaces was analyzed by means of cross-sectional SEM micrographs, as shown in Figures 2a and 2b, respectively.…”
Section: Morphology and Antireflection Effect Of Si/pedot:pss Composimentioning
confidence: 66%
“…The reduced reflectance of the hybrid solar cells that had the micro-pyramidal surfaces significantly contributed to the increased PCE value of 8.25%, in comparison to the PCE value of 1.72% of planar hybrid solar cells [11] . Therefore, the construction of an optimal textured configuration can induce conditions conducive to the enhancement of antireflection capabilities and PCE values.…”
Section: Effect Of Texture Of Antireflection Layer On Photovoltaicmentioning
confidence: 97%
See 1 more Smart Citation
“…At a low rate, the surface tension of the PEDOT:PSS solution makes it hard to penetrate into the valleys surrounded by pyramids. The increasing spin-coating rate could enhance the penetration rate and the adhesiveness of PEDOT:PSS solution on the micro-pyramidal surface [ 26 ]. The coverage area is expanded with spin-coating rate; the voids become so small that the PEDOT:PSS could nearly conformal contact with the textured substrates.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig. 5 , the contact junction areas between PEDOT:PSS film and the top of pyramids are so small that PEDOT:PSS film cannot collect enough charge, resulting in a poor heterojunction [ 26 , 27 ]. In addition, due to the wide bandgap of PEDOT:PSS, PEDOT:PSS film could reduce the interface recombination velocities and block electrons from recombination at the front surface of device.…”
Section: Resultsmentioning
confidence: 99%